Pola Utilization of Nature Tourism Locations for Socio-Economic Life of Tigaras Village Community, Dolok Pardamean District, Simalungun Regency - Corry Turnip (Trigin Publisher, 2022)
Garoga Beach and Paris-Paris Beach in Tigaras Village are one of the tourist attractions that are one of the choices in Simalungun Regency. Before becoming a tourist location, Tigaras Village was still isolated and this area was only used as an alternative route to cross to Tomok (Samosir Island). From this problem, the question arises how the pattern of utilization is carried out by the surrounding community for socio-economic life. The purpose of this study was to determine how the pattern of utilization of natural tourist sites for the socio-economic life of the community in Tigaras Village, Dolok Pardamean District, Simalungun Regency. The sociological theory used in this research is using Robert K. Merton's analytical theory of Structural Functionalism. This theory emphasizes order in society. The main concepts are functional, dysfunction, latent function, manifest function, and balance, in connection with Merton's theory that the pattern of utilization of natural tourist sites for the socio-economic life of the community brings great functions and benefits to the people of Tigaras Village, especially those in tourist sites. The results of the study show that the pattern of utilization carried out by the surrounding community is bottom-up (from bottom to top), a management concept that puts the community as the main actor in the utilization process at every stage, including the planning, implementation and evaluation processes of tourism development. The natural tourist locations of Garoga Beach and Paris-Paris Beach exist and develop because of the will and hard work of the surrounding community who organize and manage the beach into a comfortable, beautiful and suitable place for vacation so that it attracts tourists to visit. The values contained in the utilization of Tigaras Village tourist sites include recreational, educational and economic values.